THE EPIDEMIOLOGICAL FACTORS INFLUENCING PULMONARY TUBERCULOSIS INCIDENCE AMONG MIDLIFE ADULTS IN WEST JAVA 2023: Faktor Epidemiologi yang Memengaruhi Kejadian Tuberkulosis Paru Dewasa Paruh Baya di Jawa Barat Tahun 2023 - Hafsari, Kurnianty Indah; Ekaria, Ekaria (Jurnal Berkala Epidemiologi, 2026)
Background: Tuberculosis (TB) remains a challenge in achieving the third goal of the SDGs. Indonesia ranks second globally in TB cases, with West Java Province recording the highest numbers since 2019 and primarily affects midlife adults (45–64 years old). The number of TB cases in this province tends to increase each year, despite the TB case detection target having been surpassed. Purpose: This study aims to identify variables from host, agent, and environment factors influencing pulmonary TB incidence among midlife adults in West Java Province in 2023. Methods: Data were obtained from the 2023 Indonesian Health Survey. The analysis method applied was binary logistic regression with the Penalized Maximum Likelihood Estimation (PMLE) in a sample of 13,157 midlife adults. Results: This research showed that significant variables include the interaction of smoking history (host factor), pulmonary TB contact (agent factor), and exposure to cigarette smoke (environment factor) (p = 0.00, OR = 12.21), followed by host factor such as nutritional status (p = 0.00, OR = 6.72), history of Diabetes Mellitus (DM) (p = 0.00, OR = 4.66), sex (p = 0.01, OR = 2.20), and employment status (p = 0.03, OR = 2.04). Conclusion: The pulmonary TB incidence among midlife adults is most at risk for those who have smoked and are accompanied by pulmonary TB contact and exposure to cigarette smoke. Local governments need to provide outreach on the dangers of active and passive tobacco smoke, particularly for households with TB patients, to reduce the risk of transmission.